THE WAYANG STORY IN MODERN INDONESIAN FICTIONS (Reviews on Mangunwijaya and Sindhunata’s Novels) - Nurgiyantoro, Burhan (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2019)
The wayang story is the traditional story which influences toward the writing of modern Indonesian literature. This study is aimed at describing the adoption of aspects of stories in the wayang stories plays in modern Indonesian novels with a focus on Mangunwijaya and Sindhunata’s novels; i.e. Burung-burung Manyar, Durga Umayi, and Anak Bajang Menggiring Angin. The study uses the receptional, intertextual, and discourse-analysis approaches. Results show the following findings. Character referencing from shadow-wayang stories included naming and characterizing, viz. complete adoption of names and characters of wayang figures, hypogram of simultaneous naming and characterizing, and characterizing with no naming. The hypogramming of novel plots on the shadow wayang plots includes shadow-wayang show plots and shadow-wayang story plots. Every work has its own uniqueness and it is on this uniqueness that lies the values of a fiction work. This can be seen from the development of characterization of the figures and specific and unique plots. The value substances of the wayang story are related to personal, social, and religious life matters leading to perfect lives. Shadow-wayang values in novels are discharged through signification, comparison, symbolization, characters, life principles, and behaviours functioning more as cultural guidances. Keywords: shadow wayang, modern Indonesian novels, hypogram, characterization, plot, values WAYANG DALAM NOVEL INDONESIA MODERN(Tinjauan Novel Mangunwijaya dan Sindhunata) AbstractCerita wayang adalah adalah cerita tradisional yang berpengaruh terhadap penulisan sastra Indonesia modern. Penelitian ini bertujuan untuk mendeskripsikan pemunculan aspek cerita wayang dalam novel Indonesia modern dengan fokus pada novel Mangunwijaya dan Sindhunata, yaitu Burung-burung Manyar, Durga Umayi, dan Anak Bajang Menggiring Angin. Penelitian menggunakan pendekatan resepsi, intertekstual, dan analisis wacana. Hasil penelitian menunjukkan hal-hal sebagai berikut. Perujukan penokohan dari cerita wayang mencakup penamaan dan perwatakan, yaitu pengambilan lengkap nama dan karakter tokoh wayang, hipogram penamaan dengan perwatakan sekaligus, dan perwatakan tanpa disertai penamaan. Hipogram plot novel pada plot wayang mencakup plot pertunjukan wayang dan plot cerita wayang. Tiap karya memiliki keunikannya sendiri dan di situlah antara lain letak nilai sebuah karya fiksi. Hal itu terlihat pada pengembangan karakter tokoh, plot yang khas dan unik. Substansi nilai-nilai cerita wayang berkaitan dengan masalah kehidupan pribadi, sosial, dan religius yang bermuara untuk mencapai kesempurnaan hidup. Nilai-nilai wayang dalam novel disampaikan lewat pembandingan, pelambangan, simbolisasi, karakter, sikap hidup, dan perilaku tokoh yang lebih berfungsi sebagai acuan kultural. Kata Kunci: wayang, novel Indonesia modern, hipogram, penokohan, plot, nilai-nilai